2008
DOI: 10.1002/jgm.1154
|View full text |Cite
|
Sign up to set email alerts
|

Construction of X‐ray‐inducible promoters through cis‐acting element elongation and error‐prone polymerase chain reaction

Abstract: A sensitively responsive promoter to radiation could be constructed using this method, possibly leading to the construction of a promoter of interest that could be applied for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…In this report, we showed that a promoter responsive to radiation in prostate cancer cells was successfully constructed by a method described in our previous study, 18 although a set of cis-acting elements used were somewhat different. Combining a DNA fragment A radiation-responsive artificial promoter A Morii et al constructed by using randomly connected five different cis-acting elements to another DNA fragment containing the TATA-box, we constructed a promoter library.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this report, we showed that a promoter responsive to radiation in prostate cancer cells was successfully constructed by a method described in our previous study, 18 although a set of cis-acting elements used were somewhat different. Combining a DNA fragment A radiation-responsive artificial promoter A Morii et al constructed by using randomly connected five different cis-acting elements to another DNA fragment containing the TATA-box, we constructed a promoter library.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a constructed promoter library tends to contain many promoters responsive to radiation stimulation and thus, it would not be a very difficult task to obtain a useful promoter out of such a library by screening (Figure 1c). 18 Therefore, it should not be impractical to construct promoters for individual cancer treatments. In addition, one promoter could be used for the treatment of multiple types of cancer as it was shown that clone 880-8 was activated by radiation in five cell lines out of 11 different cell lines tested (Figure 2e).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations